PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS E-LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Adek Nilasari Harahap; Jainal Abidin (JURNAL MathEdu (Mathematic Education Journal), 2021)
E-learning-based interactive mathematics teaching materials are a means of learning mathematics that can be used by educators to assist students in the learning process using electronics such as mobile phones and computers. The teaching materials also help educators and students learn outside of school and at a distance. The research method used is Research and Development (R&D) based on the 4D research and development model. The stages carried out are the defining stage, the planning stage (design), the development stage (develop), and the dissemination stage (disseminate). The results of the validation of teaching materials obtained on the feasibility aspect of the content are 3.58, the linguistic aspect is 3.67 and for the presentation feasibility aspect is 3.53. Student learning outcomes come from the pre-test and post-test scores. The average score of students in the pre-test activity was 40.25, while the post-test was 82.19.